Study of Variations in Concentration of Stearic Acid and Amonium Molybdate on Physical Characteristics of Bioplastic Smart Packaging - Chandani, Ni Putu Ayu Prya; Yulianti, Ni Luh; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Smart packaging is packaging that has the ability to provide information about the quality of packaged products directly by utilizing a number of compounds that act as indicators of the quality of the packaged product, so that research on smart packaging is feasible. This study was conducted to obtain the influence of stearic acid concentrations and ammonium molybdate on the physical characteristics of bioplastic smart packaging; determine the treatment that produces the physical characteristics of the best bioplastic smart packaging according to SNI and get the response of bioplastic smart packaging indicators to the maturity level of avocado fruit. This study used a two-factor Randomized Group Design. The first factor is the stearic acid concentration which consists of 3 levels, specifically 0.4%, 0.5% and 0.6%. The second factor is the concentration of ammonium molybdate which consists of 3 levels, specifically 1g, 2g and 3g. The results showed that the interaction between treatments had a significant influence on the parameters of elongation, tensile strength, swelling, thickness and elasticity. The best treatment was obtained in the use of stearic acid concentration of 0.4% and 1g of ammonium molybdate which resulted in a tensile strength value of 13.85 MPa, elongation value of 3.60%, an elasticity value of 384.93 MPa, a swelling value of 0.81% and a bioplastic thickness value of 0.23 mm. The conclusion of this study is that the treatment of stearic acid concentration of 0.4% and 1g of ammonium molybdate is the best treatment that is able to respond to the maturity level of avocado fruits in the form of a change in the color of the resulting packaging.